(untitled) (Trabalho & Educação, 2022)
Occupational divisions in any country are understood largely as change in the activities of the membersin a given society and the way to earn their livelihood. Mostly, the change is observed in terms of changes in the distribution activities in the socio-economic structure of the society. India is a traditional caste-based society and so it is pertinent to describe occupational activities in terms of socio-cultural rather than the socio-economic structure. The socio-cultural implications of these occupational changes of the communities’ opted alternative occupational options and understanding their development, requires interrelations of various aspects with holistic approach. The researchers felt that there is inadequacy of empirical studies relating to socio-cultural, economic and political attributes of different occupational groups. The point of departure of this paper is the caste affirmation and its ramifications on traditional communities by claiming their traditional occupations for new social identity. This affirmation in turn is expected to lead to a shift in the socio-political relationships of the community with the other dominant communities in social hierarchy. In India, occupational changes are taking place more widely than statistical changes and emerging with alternative social movement. This paper also critically analyses the existing caste theories, lacuna in the existing nomenclature, and gives a glimpse of Constitutional Privileges and their reflection on contemporary Government Orders (GOs) with special reference to a community (Scheduled Caste) in Tamil Nadu (State in South India). The paper empirically validates the emerging alternative collective social movement of a community, their social status through traditional occupation, knowledge system and their resistance to inclusion in the existing nomenclature